STOCHASTIC VOLATILITY APPROACH TO THE HESTON MODEL IN EX-TRADED MUTUAL FUNDS (ETF´s) (Journal of the Faculty of Accounting, Economics and Administrative Sciences -FACCEA, 2024)
In this study, we model the growth rate and daily volatility of a set of exchange-traded funds (ETFs) with a periodicity from 2018 to 2023. First, we organize the data to derive the initial parameters. We then use the maximum likelihood estimate together with the data from each ETF to calibrate the parameters of the Heston model. Finally, we use the calibrated parameters to simulate 1,000 trajectories for each ETF over a period of one trading year. The study found that the SOXL ETF had the best annual performance, while the XLF ETF had the lowest. The LABU, FXI, IWM, and SOXL ETFs were more volatile and had negative correlations with their underlying indices, while the PSQ, OLK.IL, and XLF ETFs were less volatile and had positive correlations. Finally, reduced-risk investments were discovered, including the low volatility PSQ ETF and the moderately volatile but positive growth rate SPY ETF. On the other hand, riskier assets were discovered, including the highly volatile LABU ETF and the extremely volatile SOXL ETF with a negative growth rate.